1977
DOI: 10.1007/bf01223267
|View full text |Cite
|
Sign up to set email alerts
|

Serum high density lipoprotein in diabetic patients

Abstract: Summary. The purpose of the present investigation was the study of HDL lipoprotein changes in patients with diabetes mellitus. The comparison was made between 40 normal and 109 diabetic subjects and the following data was obtained: relative HDL concentration (polyacrylamide gel electrophoresis), HDL-cholesterol and apolipoprotein A concentrations. We found significant decreases in HDL (18-28%) and HDL-cholesterol (31-40 rag/ 100 ml) in most diabetics except in those with normalized serum levels of glucose an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

1979
1979
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(36 citation statements)
references
References 18 publications
(20 reference statements)
1
34
0
1
Order By: Relevance
“…The lipoprotein pattern of these diabetics was characterized by an increase of VLDL, slight elevation of LDL and decrease of HDL-cholesterol. Elevated VLDL and total triglyceride combined with low HDL-cholesterol has been recently described in a number of studies in adultonset type diabetes [15][16][17][18]. Schonfeld et al [15] have found that both LDL and HDL are enriched in triglycerides in adult onset type diabetics even without any elevation of serum lipid levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lipoprotein pattern of these diabetics was characterized by an increase of VLDL, slight elevation of LDL and decrease of HDL-cholesterol. Elevated VLDL and total triglyceride combined with low HDL-cholesterol has been recently described in a number of studies in adultonset type diabetes [15][16][17][18]. Schonfeld et al [15] have found that both LDL and HDL are enriched in triglycerides in adult onset type diabetics even without any elevation of serum lipid levels.…”
Section: Discussionmentioning
confidence: 99%
“…The biochemical basis of this relationship lies probably in the fact that part of plasma HDL (mainly HDL2) is generated in the circulation by transfer of cholesterol, phospholipids and apoproteins from triglyceride-rich lipoproteins to HDL during the degradation of the former by endothelial LPL [30][31][32][33][34]. Thus, the low HDL levels observed in both insulin-deficient as well as in adult onset type insulin resistant diabetes [15][16][17][18] could be accounted for by depletion of the insulin-sensitive endothelial LPL The observed slow response of HDL to insulin treatment also fits to this hypothesis since the full replenishment of tissue LPL activity after initiation of insulin treatment appeared also to take relatively long time.…”
Section: Discussionmentioning
confidence: 99%
“…Samples for triacylglycerol, total (Seidel et al, 1983;Kattermann et al, 1984;Wahlefeld, 1974). HDLcholesterol was measured after sedimentation of apo-lipoprotein-B-containing lipoproteins with magnesium-phosphorus-wolfram acid (the precipitant method; Burstein et al, 1970;Lopes-Virella et al, 1977) also from Boehringer, Mannheim. The plasma was measured on a Cobas Mira S (Boehringer Mannheim GmbH, Germany).…”
Section: Laboratory Sampling and Analysesmentioning
confidence: 99%
“…HDL-Cholesterol was measured in fresh serum (Lopes-Virella et al 1977), and serum LDL-C was calculated from the following formula (Friedewald et al 1972): LDL-C (mg/dl) = TC -[HDL-C + (TG/5)], while atherogenic index was calculated from the following formula (Sagud et al 2009): Atherogenic index = LDL-C / HDL-C The liver glycogen was determined using EnzyChromTM Glycogen Assay Kit (Murat and Serfaty 1974).…”
Section: Experimental Designmentioning
confidence: 99%